Influence of cadence, power output and hypoxia on the joint powers and muscle excitation during cycling - Sanderson, D. J.; Mornieux, G.; Guenette, J. A.; Sheel, A. W. (2008 Annual Meeting (NACOB) Ann-Arbor, 2008)
Analysis of the relative joint distribution to the global lower-limb activity was initially presented by Ericson et al. (1986). They described the percentage contribution of each joint to the total positive and negative work and reported that the main relative energy producers were the knee extensors (39%) and the hip extensors (27%), whereas the plantar flexors (57%) and the hip extensors (32%) were the main relative energy absorbers at 120 W and 60 rpm. Ericson (1988) described the influence of pedalling cadence and power output on the relative proportions of the total positive work at the hip, knee, and ankle joints. Pedalling cadence was found to have no influence, while power output showed only a significant effect on the hip flexors and ankle extensors, both decreasing their proportions with increased power output from 0 to 240 W. Recently, Mornieux et al (2007) provided data showing the relative insensitivity of the ankle, knee, and hip joint moment to variations in cadence and power output. Even in the presence of hypoxia this relative insensitivity remained. The data presented here came from the same project and expand on the notion of insensitivity.